PENEGAKAN HUKUM LINGKUNGAN DALAM PENGELOLAAN SAMPAH DI PASAR WOLOWONA KELURAHAN REWARANGGA SELATAN KECAMATAN ENDE TIMUR KABUPATEN ENDE - Bambut, Maria M S; Nuban, Detji K E R; Tuan, Yohanes (Petitum Law Journal, 2025)
The issue of waste management in Indonesia, particularly in Ende Regency, remains a significant challenge that threatens environmental quality and public health. Population growth and economic activities that are not balanced with adequate waste management lead to various negative impacts, such as environmental pollution, soil degradation, and health problems. This study aims to analyze law enforcement in waste management at Wolowona Market, Ende Regency, by focusing on the implementation of Ende Regency Regional Regulation No. 8 of 2014 on Waste Management. The method used is empirical research, with primary data obtained through interviews and observations. The results show that law enforcement in waste management at Wolowona Market is still suboptimal, marked by insufficient supporting facilities, low public awareness, and weak legal actions against violations. Efforts such as socialization, community service, and inter-agency collaboration have been carried out, but limitations in human resources, budget, and coordination remain major obstacles. This study recommends enhancing law enforcement, including strict administrative sanctions, provision of adequate facilities, and intensive public awareness campaigns. Collaboration between the government, community, and business actors is also key to creating more effective and sustainable waste management that supports environmentally sound development.